Firm's Obstacles and Survival: The Study of Firm's Life Cycle and Obstacles in Indonesia - ardianti, retno (Jurnal Manajemen Teknologi, 2013)
Research regarding firms life cycle have been carried out for years with varying models and different emphasis. The purpose of this study is to test differences of obstacles in each different stages of firm's life cycle and differences in perceiveing the level obstacles from top managers' different individual background by using Olawale & Garwe (2010) obstacles indicators and Timmons (2007) model of firm's life cycle. Data was taken from 831 firms covering small, medium, and large firms in Indonesia which experienced all thirteen obstacles. Findings show significant differences on obstacles among firms that are in different stages of life cycle,which firms in maturity and stability stage tend to experience greater level of obstacles compare to firms in earlier stages. Findings also found significant differences on top manager's education in perceiving firms obstacles, with manager from higher education background shows higher score in perceiving obstacles, while gender and length of managerial experience shows no significant differences in perceiving obstacles.Keywords: Small and Medium Enterprise, Firm's Life Cycle, Obstacles, Survival, Individual Background